Media convergence in social communication and cyberculture - Yessenbekova, Ұ.М.; Mamankul, А.Ә.; Syzdykova, А.А.; Kutym, Б. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2023)
The article is devoted to a theoretical study of the role of media convergence in the formation of social communication and cyber culture. Comprehensive analysis showed that the convergence of mass media has become a defining factor in the interaction between people and the media. During the discussion of various aspects of media convergence and its place in public relations, connections with traditional culture, scientific conclusions were drawn. The study found how media convergence contributes to the development of cyberculture. People actively interact through social networks, forums, blogs and other online platforms, forming their own digital communities and groups. In the virtual space, they share their knowledge, interests and new ideas, thus creating modern forms of cyberculture. The authors showed that media convergence, driven by such active connections, increases the accessibility and convenience of information and entertainment. The final results of the article confirm that media convergence is an important determining factor in the formation of social communication and cyber culture. The influence of convergence on the relationship between people and the trajectory of the development of the information society as a whole is assessed. The findings of the study show that the study of convergent trends in the mass media helps to predict the development of the state and society, to develop strategies that direct social communication and virtual culture in a direction that is useful for society.